Felsinschriften auf Kafrije/Kafranarti einem Riff im Fluss zwischen Elephantine und Aswân - Seidlmayer, Stephan Johannes 1957- (2023)
Kafranarti/Kafriye, a small rocky island in the river between Aswan and Elephantine, is graced by a number of beautiful rock reliefs belonging to members of a family of treasury officials from the time of Amenhotep Ill. From the same period, and partly from the same people, stems another set of rock reliefs close by on the steep rock face below the public garden of Aswan. A new, full documentation of these inscriptions is offered along with some comments on their topographical location.
Keywords: Aswan; Kafranarti; rock inscriptions; Epigraphy; Prosopography